2021
DOI: 10.3389/fchem.2021.651281
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Triple Symmetric Non-halogen Benzene Derivative Solvent for Spray-Coated Polymer Solar Cells

Abstract: The performance of spray-coated polymer solar cells could be largely improved via morphologies and phase optimization by solvent engineering. However, there is still a lack of fundamental knowledge and know-how in controlling blend morphology by using various solvents. Here, the effect of adding low polar benzene and non-halogen benzene derivatives with triple symmetric molecular has been systematically investigated and discussed. It is found that the triple symmetric non-halogen benzene could promote the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…To minimize the presence of trap states, it is necessary to reduce the density of structural defects in the active layer of OPV devices. This requires a careful optimization of the stacking properties of organic molecules in the active layer. , Existing studies have demonstrated that the use of high-boiling-point solvents with a lower evaporation rate is an effective approach to achieve a more desired molecular stacking structure, thereby reducing the density of structural defects. For instance, Hu et al reported that compared to low-boiling-point carbon disulfide solvents, the utilization of high-boiling-point ortho-dichlorobenzene as a processing solvent for P3HT:PCBM active layers allows sufficient time for self-organization during a gradual drying process, resulting in less structural defects and the formation of the optimal active layer morphology . Therefore, to mitigate the influence of trap-assisted recombination, limiting the performance of OPV devices under low illumination intensities, we intend to employ a commonly used high-boiling-point solvent for device fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the presence of trap states, it is necessary to reduce the density of structural defects in the active layer of OPV devices. This requires a careful optimization of the stacking properties of organic molecules in the active layer. , Existing studies have demonstrated that the use of high-boiling-point solvents with a lower evaporation rate is an effective approach to achieve a more desired molecular stacking structure, thereby reducing the density of structural defects. For instance, Hu et al reported that compared to low-boiling-point carbon disulfide solvents, the utilization of high-boiling-point ortho-dichlorobenzene as a processing solvent for P3HT:PCBM active layers allows sufficient time for self-organization during a gradual drying process, resulting in less structural defects and the formation of the optimal active layer morphology . Therefore, to mitigate the influence of trap-assisted recombination, limiting the performance of OPV devices under low illumination intensities, we intend to employ a commonly used high-boiling-point solvent for device fabrication.…”
Section: Resultsmentioning
confidence: 99%